2011
DOI: 10.1002/nme.3282
|View full text |Cite
|
Sign up to set email alerts
|

A framework for coupled deformation–diffusion analysis with application to degradation/healing

Abstract: SUMMARYThis paper deals with the formulation and numerical implementation of a fully coupled continuum model for deformation-diffusion in linearized elastic solids. The mathematical model takes into account the effect of the deformation on the diffusion process, and the affect of the transport of an inert chemical species on the deformation of the solid. We then present a robust computational framework for solving the proposed mathematical model, which consists of coupled non-linear partial differential equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…It will also be shown that many popular models are special cases of the proposed mathematical model. For example, we will show that the small-strain moisture degradation model proposed in [Mudunuru and Nakshatrala, 2012] is a special case of the proposed model. (ii) We will calibrate the proposed degradation model with existing experimental data sets.…”
Section: Degradation Factormentioning
confidence: 99%
See 1 more Smart Citation
“…It will also be shown that many popular models are special cases of the proposed mathematical model. For example, we will show that the small-strain moisture degradation model proposed in [Mudunuru and Nakshatrala, 2012] is a special case of the proposed model. (ii) We will calibrate the proposed degradation model with existing experimental data sets.…”
Section: Degradation Factormentioning
confidence: 99%
“…Status of the degradation model in [Mudunuru and Nakshatrala, 2012]. The small-strain chemo-mechano degradation model proposed in [Mudunuru and Nakshatrala, 2012] is a special case of the proposed chemo-thermo-mechano degradation, and can be obtained under a plethora of assumptions. These assumptions include steady-state response, small strains, and isothermal conditions with negative volumetric heat source in the entire degrading body.…”
Section: A General Constitutive Model For Chemo-thermo-mechano Degradmentioning
confidence: 99%
“…Material degradation is a common phenomenon and affects its mechanical parameters [55,56]. Before node failure, the damage variable remains zero and Young's modulus stays constant.…”
Section: Relationship Between Damage and Permeabilitymentioning
confidence: 99%
“…The current computing power available has allowed for complex fracture models to be applied to a wide range of length scales [31,32]. Of these, many continuum (or macro-scale) and phase-field modeling approaches [33][34][35][36][37][38][39] have been developed to address crack evolution and the overall material response in large samples (cm-scale and larger) including finite element methods [40][41][42] and boundary element methods [43,44]. Continuum-based approaches [45] assume that the computational domain can be treated as one continuous body.…”
Section: Introductionmentioning
confidence: 99%